Pengaruh Media Sosial TikTok dan Produk Wisata 4A Terhadap Minat berkunjung Wisatawan ke Desa Wisata Pesona Bukit Cinta di Kabupaten kerinci - Veyka Gusfi Diaz Aura (Journal of Tourism Sciences, Technology and Industry, 2026)
This study aims to analyze the influence of the social media platform TikTok and 4A tourism products on touristsâ€™ interest in visiting the Pesona Bukit Cinta Tourism Village in Kerinci Regency. This study employs a quantitative approach using a survey method. The research sample consisted of 110 respondents selectedÂ using purposive sampling. Data collection was conducted through the distribution of questionnaires and analyzed using SPSS version 29 via descriptive analysis, instrument validation, classical assumption tests, t-tests, and multiple linear regression analysis.The results of the descriptive analysis indicate that the variables of the TikTok social media platform, the 4A tourism products, and touristsâ€™ interest in visiting fall into the â€œgoodâ€ category. The social media platform TikTok was assessed as effective for promoting and disseminating destination information, while the 4A tourism productsâ€”which include attractions, accessibility, amenities, and ancillary servicesâ€”were able to meet touristsâ€™ expectations. The t-test results showed that the social media platform TikTok had a positive and significant effect on touristsâ€™ interest in visiting, with a calculated tvalue of 4.919, which is greater than the critical t-value of 1.984, and a significance level of < 0.001. The 4A tourism products also have a positive and significant effect on touristsâ€™ interest in visiting, with a calculated t-value of 3.991, which is greater than the critical t-value of 1.984 and a significance level of < 0.001. Based on the research results, it can be concluded that the social media platform TikTok and the 4A tourism product have a positive and significant effect on touristsâ€™ interest in visiting Pesona Bukit Cinta Tourism Village in Kerinci Regency. Therefore, the optimization of TikTokâ€™s utilization and the improvement of the quality of the 4A tourism product need to be continuously pursued to increase touristsâ€™ interest in visiting Pesona Bukit Cinta Tourism Village in Kerinci Regency.